Trapezius activity and intramuscular balance during isokinetic exercise in overhead athletes with impingement symptoms - Cools, A. M.; Declercq, G. A.; Cambier, D. C.; Mahieu, N. N.; Witvrouw, E. E. (Scandinavian Journal of Medicine & Science in Sports, 2007)
We compared normalized trapezius muscle activity and intramuscular balance ratios between overhead athletes with impingement symptoms and non-injured athletes during isokinetic abduction and external rotation movements. Thirty-nine overhead athletes with chronic impingement symptoms and 30 non-injured athletes participated in the study. Electromyographic activity of upper, middle, and lower trapezius was measured during isokinetic abduction and external rotation, using surface electrodes. The results show a significant increase of upper trapezius activity during both movements in the patient group, with decreased activity in the lower trapezius during abduction, and in the middle trapezius during external rotation. Analysis of the intramuscular activity ratios revealed muscle imbalance on the injured side of the patient group for upper/middle trapezius and upper/lower trapezius during abduction, and for all three muscle activity ratios during external rotation. These results confirm the presence of scapular muscle imbalances in patients with impingement symptoms and emphasize the relevance of restoration of scapular muscle balance in shoulder rehabilitation.